Varied influence of the femoral or tibial component on quadriceps angles: Verified by imaging studies - Chi-Chuan Wu; Kee-Min Yeow; Yun-Jen Yeow (Acta Orthopaedica et Traumatologica Turcica)
Objective: The aim of this study was to evaluate the varied influence of femoral or tibial component on Quadriceps angles (Q-angle) measured with magnetic resonance image (MRI) and full-length standing scanogram (FLSS) techniques. Methods: Two groups of patients were studied. The first group underwent MRI studies and the second group underwent FLSS studies. Two-step procedures were carried out. Knee MRI in 60 consecutive adult patients simply taken for meniscus or ligament injuries were utilized at the first step. The standardized patellar center (PC) and tibial tubercle (TT) on the frontal plane of MRI were positioned. At the second step, the FLSS in other 100 consecutive young adult patients taken for chronic unilateral lower extremity injuries were used for locating the two landmarks from MRI. The Q-angle was then determined on the anterior superior iliac spine, standardized PC, and TT on the FLSS. Results: For 60 patients, the standardized PC was at the point 42% from the lateral end of the trans-epicondylar line of the femur. The TT was at the point 2 cm distal to the tibial articular surface and 37% from the lateral end of the tibial width. For 100 patients, the Q-angle was an average of 9.5° and 65.2% of the Q-angle was contributed by the upper arm (the femur). Women had a larger Q-angle (10.1° vs. 8.8°, p = 0.02) and a shorter femur (41.1 vs. 44.7 cm, p < 0.001). Conclusion: The Q-angle is about 9.5° with 65.2% contributed by the femur. The Q-angle may mainly be influenced by the femoral component. Level of evidence: Level IV, Diagnostic Study. Keywords: Femoral component, Full-length standing scanogram, Influence, Magnetic resonance images, Quadriceps angle, Tibial component